PENGARUH PROGRAM THE NEWSROOM NET TV TERHADAP PENGETAHUAN MAHASISWA DALAM PROSES PELIPUTAN BERITA TELEVISI DI JURUSAN ILMU KOMUNIKASI UNIVERSITAS RIAU - Agidatul Izzah; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Newsroom program can provide knowledge to students about the television news coverage process. This program is broadcast on NET TV every Saturday at 18.00 WIB. The newsroom explains how the real world of work is, especially for students who will carry out internships. The theory used in this study is the theory of S-O-R (Stimulus-Organism-Response). The purpose of this study was to determine how much influence the NET TV Newsroom program has on student knowledge in the process of covering television news in the University of Riau Communication Science department.   This research uses quantitative research methods, with data collection techniques, namely through questionnaires. The sample in this study amounted to 96 respondents, namely drawn by using the Unknown Population formula. The selected respondents were Riau University Communication Science students from the class of 2012 to 2018 who watched The Newsroom program, to divide into years of force used the Propotional Random Sampling formula. The data analysis method used is simple linear regression analysis. Data processing is done with the SPSS version 21 program. The results of the study with The Newsroom program variable coefficient of 0.756 and a significance value of 0,000 smaller than α = 0.05, which means that the Newsroom program has an influence on the knowledge of students of Communication Sciences. Meanwhile t count 8.023 is greater than t table which is 1.986. Based on the statistics obtained, the hypothesis received in this study is that there is a large influence of the Newsroom program on student knowledge in the television news coverage process in the University of Riau Communication Science department. Based on the test results the coefficient of determination shows the Rsquare value of 0.406 which means there is an influence of 40.6%. While the remaining 59.4% is influenced by other variables not included in this study.